Music As An Integrated Education Tool for Preschool Students - Wadiyo, W (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2015)
Integrated study is considered to be important for preschool students. This study is aiming at understanding the implementation of learning music in integrated learning context in preschool education level especially kindergarten. Research methodology employed in this research was qualitative method. The subject of this study was the implementation of learning in preschool education level especially kindergartens in Semarang. This study focuses on how music or children song is used as integrated education tool by the teacher. Observation, interview and study of documentation were implemented here as the data collection technique. In addition, source triangulation technique was applied here as the validation technique, while interactive analysis was used as the data analysis technique. Results of the research show that the application of learning music process in preschool level of kindergarten school in Semarang is integrated with the other lessons. The development of its learning materials refers to the curriculum by considering the developments of the children in general. The main technique in the implementation of the learning process is by singing together. Messages of the music or song are used in order to deliver the education message according to the theme of learning.